Scientific medicine and the belief in the supernatural - Lavado Landeo, Lincoln (2024)
Magic, witchcraft and miracles have accompanied medicine since the beginning of mankind. At first, the causes of diseases were belived to be supernatural, but progressively, with the development of knowledge and the advent of science, morerational and objective explanations were found.Rationality was based on concepts, judgments and reasoning that followed logical rules. All of these elements then formed new ideas, which did not accumulate chaotically but were organized into sets and ordered systems, called theories.Objectivity, in turn, was related to the search for factual truths that aligned with the object of study, confirming that ideascorresponded with the facts through observation and experimentation, thus making them reproducible.During their evolution, the new ideas were confronted with numerous theological prejudices, especially in the Middle Ages. This period was dominated by Catholic Christianity and caused a severe stagnation of medicine. Religion and superstition hindered progress: people believed in the efficacy of sacred relics and the laying on of hands as well as indiabolical possessions and healing through miracles.In this evolution, many thinkers stopped to seriously reflect on and analyze what miracles actually were. Among many philosophers, it was the Dutch Baruch Spinoza and the English David Hume, who in the 17th and 18th centuries, respectively,provided the clearest and most compelling answers. Even in the 21st century, despite the successes of scientific medicine, many people continue to believe in supernatural healings. Modern science maintains that these cases arise due to errorsin critical thinking, misunderstandings or the use of flawed logic.This article attempts to explain the reasons that promote the persistance of this type of mindset, how pseudomedicine uses it and how we can address events that seem inexplicable, especially in the medical field.Objectivity and reason have given us centuries of progress, and we must not abandon them. True "miraculous healings" are the result of the hard and careful work of scientists, physicians and researchers.